(untitled) (Acta Scientiarum. Animal Sciences, 2025)
The poultry feed industry in Cameroon faces high costs due to its dependence on imported ingredients like shellfish meal, a key calcium source. To promote animal feed self-sufficiency and reduce imports, this study evaluates Figuil limestone as a local alternative. The effects of replacing shellfish meal with limestone meal on Japanese quail (Coturnix japonica) were assessed in terms of growth, carcass traits, and reproduction. A total of 300-day-old quails were divided into 15 groups. Five diets with increasing substitution levels of shell meal by limestone meal (0, 25, 50, 75, 100%) were tested, with each treatment replicated three times. At 7 weeks, six birds per batch were sampled for biochemical and carcass analysis. Results showed that feed intake increased with limestone inclusion, while growth, carcass, and organ traits remained unaffected. A 50% substitution level improved the laying rate (24.9±2.2%) compared to the control (20.0±6.9%), though control birds had heavier eggs (12.1±0.1 g). Limestone also increased Haugh Units and edible content but reduced shell thickness. Biochemical parameters showed no significant differences. The study concluded that Figuil limestone can be an effective substitute for shellfish meal in quail diets, with 50% replacement level being the most effective during the early laying period.